Effects of long time exposure to simulated micro- and hypergravity on skeletal architecture. (November 2015) - Canciani, Barbara; Ruggiu, Alessandra; Giuliani, Alessandra; Panetta, Daniele; Marozzi, Katia; Tripodi, Maria; Salvadori, Piero A; Cilli, Michele; Ohira, Yoshinobu; Cancedda, Ranieri; Tavella, Sara
Abstract: This manuscript reports the structural alterations occurring in mice skeleton as a consequence of the longest-term exposition (90 days) to simulated microgravity (hindlimb unloading) and hypergravity (2 g ) ever tested. Bone microstructural features were investigated by means of standard Cone Beam X-ray micro-CT, Synchrotron Radiation micro-CT and histology. Morphometric analysis confirmed deleterious bone architectural changes in lack of mechanical loading with a decrease of bone volume and density, while bone structure alterations caused by hypergravity were less evident. In the femurs from hypergravity-exposed mice, the head/neck cortical thickness increment was the main finding. In addition, in these mice the rate of larger trabeculae (60–75 μm) was significantly increased. Interestingly, the metaphyseal plate presented a significant adaptation to gravity changes. Mineralization of cartilage and bone deposition was increased in the 2 g mice, whereas an enlargement of the growth plate cartilage was observed in the hindlimb unloaded group. Indeed, the presented data confirm and reinforce the detrimental effects on bone observed in real space microgravity and reveal region-specific effects on long bones. Finally these data could represent the starting point for further long-term experimentations that can deeply investigate the bone adaptation mechanisms to different mechanical force environments. Graphical abstract: Highlights: The longest exposure to HLU and hypergravity ever tested affect bone architecture. Hindlimb-unloading induces bone mass and cortical thickness decrement. Trabecular compartment histomorphometry was clearly altered by HLU. Hypergravity induce thickening in cortical bone and larger-sized trabeculae. Hypergravity and HLU alter the mineralized cartilage layer of the femur growth plate.